Mapping research in Socio-pragmatic linguistics on food vloggers on YouTube: A bibliometric analysis - Rahman, Fauzi; Rafli, Zainal; Anwar, Miftahulkhairah (LingTera, 2024)
The phenomenon of food vloggers sharing their culinary experiences through videos presents an interesting area for sociopragmatic studies. This research focuses on understanding the social interactions and pragmatic contexts within food vlogging content. Specifically, the study aims to map the development of sociopragmatic research on the YouTube platform in relation to food vlogging. Using qualitative methods and bibliometric analysis, this study identifies and analyzes publications related to sociopragmatics and food vlogging from electronic databases such as Web of Science, Scopus, and Google Scholar. Keywords such as "sociopragmatics," "food vlogging," and "YouTube" were used to gather relevant data. Bibliometric analysis was conducted using Publish or Perish and VOSviewer software, enabling the processing and visualization of data in this field. The findings indicate a growing interest in food vlogging as a research subject, although studies explicitly examining sociopragmatic aspects remain limited. These findings highlight opportunities for in-depth research on sociopragmatic aspects, such as the use of speech acts, politeness in language, vloggers' communication strategies, interactions between vloggers and viewers, the construction and negotiation of social identities in vlog content, and the reflection of cultural values and social norms in social media interactions, particularly on YouTube.